2019
DOI: 10.1063/1.5126050
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between electrical properties and interface structures of SiO2/4H-SiC prepared by dry and wet oxidation

Abstract: We have investigated the relationship between the electrical properties and interfacial atomic structure of SiO2/4H-SiC interfaces, prepared by dry and wet thermal oxidation procedures with 4H-SiC (0001) and 4H-SiC (000-1) substrates, using extended x-ray absorption fine structure (EXAFS) spectroscopy and electrical methods. From the current–voltage (I–V) and capacitance–voltage (C–V) measurements, the gate leakage current onset and density of interface states were shown to depend on the thermal oxidation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The kinetics of oxidation suggest that wet oxidation is preferable due to the much shorter time required to form gate oxide [ 44 ]. Some results suggest that this process can result in lower interface state densities than conventional dry oxidation [ 45 , 46 ]. Recently, it has been shown that, during oxidation, the wet oxidation process generates lower interface stresses [ 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The kinetics of oxidation suggest that wet oxidation is preferable due to the much shorter time required to form gate oxide [ 44 ]. Some results suggest that this process can result in lower interface state densities than conventional dry oxidation [ 45 , 46 ]. Recently, it has been shown that, during oxidation, the wet oxidation process generates lower interface stresses [ 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The work reported by Hirai et al showed that wet H 2 O oxidation treatment significantly reduced the intrinsic strain of gate oxide near the interface, compared to dry O 2 oxidation [17], which may be due to the ability of H 2 O to remove the carbon-related byproducts of oxidation from the interface more efficiently than O 2 [16]. However, it is worth noting that the previous research on 4H-SiC wet oxidation was mostly performed at an environment temperature less than or equal to 1200 • C [12][13][14][15][16][17][18], which may be limited by the maximum operating temperature of the quartz furnace. Although the former researchers have reported the influence of wet oxidation on the channel mobility of 4H-SiC MOSFETs [12][13][14], the information about the effect of high-temperature wet oxidation on the integrity of gate oxide is not sufficient.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, it has been reported that thermal oxidation in wet ambience with H 2 O gas results in the improvement of 4H-SiC MOS interface quality [12][13][14][15][16][17][18]. Several previous works showed that the channel mobility of 4H-SiC MOSFETs on a-face, C-face, and Si-face can be significantly enhanced by wet oxidation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] These defects can be eliminated by POA and improved oxidation processes; [5,[11][12][13] the latter can suppress the generation of these defects fundamentally by increasing the oxidant concentration near the SiC/silicon dioxide (SiO 2 ) interface. [14][15][16] Improved oxidation processes include wet oxidation, [17] NO oxidation, [6] plasma oxidation, [18,19] and ozone (O 3 ) oxidation. [20] Although these methods can reduce the interface trap density (D it ) of SiC MOS devices to some extent, wet oxygen, NO, and plasma oxidation may lead to V th /V fb instability, [21,22] the introduction of fast traps, [23] and sample damage due to highly energetic particle bombardment, [24] respectively.…”
Section: Introductionmentioning
confidence: 99%